Genetic diversity and lack of artemisinin selection signature on the Plasmodium falciparum ATP6 in the Greater Mekong Subregion - Miao, Miao (2014)
The recent detection of clinical Artemisinin (ART) resistance manifested as delayed parasite clearance in the Cambodia-Thailand border area raises a serious concern. The mechanism of ART resistance is not clear; but the P. falciparum sarco/endoplasmic reticulum Ca(2+)-ATPase (PfSERCA or PfATP6) has been speculated to be the target of ARTs and thus a potential marker for ART resistance. Here we amplified and sequenced pfatp6 gene (~3.6 Kb) in 213 samples collected after 2005 from the Greater Mekong Subregion, where ART drugs have been used extensively in the past. A total of 24 single nucleotide polymorphisms (SNPs), including 8 newly found in this study and 13 nonsynonymous, were identified. However, these mutations were either uncommon or also present in other geographical regions with limited ART use. None of the mutations were suggestive of directional selection by ARTs. We further analyzed pfatp6 from a worldwide collection of 862 P. falciparum isolates in 19 populations from Asia, Africa, South America and Oceania, which include samples from regions prior to and after deployments ART drugs. A total of 71 SNPs were identified, resulting in 106 nucleotide haplotypes. Similarly, many of the mutations were continent-specific and present at frequencies below 5%. The most predominant and perhaps the ancestral haplotype occurred in 441 samples and was present in 16 populations from Asia, Africa, and Oceania. The 3D7 haplotype found in 54 samples was the second most common haplotype and present in nine populations from all four continents. Assessment of the selection strength on pfatp6 in the 19 parasite populations found that pfatp6 in most of these populations was under purifying selection with an average d(N)/d(S) ratio of 0.333. Molecular evolution analyses did not detect significant departures from neutrality in pfatp6 for most populations, challenging the suitability of this gene as a marker for monitoring ART resistance.